Team knowledge sharing: A game-based learning approach - N. B. H. Phung; T. Q. Dung; N. T. Duong (Образование и наука)
Introduction. Business simulation games that have been widely used in teaching in recent years have been proven to help students develop teamwork and problem-solving skills.Aim. The current research aims to assess how team cohesion and knowledge sharing attitudes relate to organisational climate and knowledge sharing (KS) intentions.Methodology and research methods. Through the use of a game-based team learning environment, this study examined the students’ attitudes and intentions regarding KS. As part of the study, questionnaires were also administered to 202 students at business colleges in Ho Chi Minh City, Vietnam. Bootstrapping estimation was used to test all hypotheses using a structural equation model (SEM).Results. The research findings showed that (1) organisational climate positively influenced team cohesion, as well as KS attitudes positively influencing KS intentions; (2) organisational climate was positively related to KS attitudes and intentions; (3) team cohesion was positively associated with KS attitudes and intentions; and (4) a significant relationship exists between organisational climate and KS intentions through the mediation of team cohesion and KS attitudes.Scientific novelty. The study helps to examine the relationships between the four variables that have been done before.Practical significance. The research findings suggest that teachers should establish grading standards and encourage students to express their opinions. In addition, it is crucial to create a good atmosphere and enhance cohesion in the class so that they can trigger students’ KS attitudes and intentions.